Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Turnover Intention Melalui Kepuasan Kerja di PT Subah Spinning Mills - Amelia Nurlaila Chasanah; Farah Chalida Hanoum; Hawik Ervina Indiworo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
High turnover intention rates are a major problem in human resource management in manufacturing companies. Turnover intention can result in significant losses for companies due to increased recruitment and training costs, as well as the loss of competent employees. This study aims to analyze the effect of compensation and the work environment on turnover intention through job satisfaction as a mediating variable at PT. Subah Spinning Mills. Compensation and the work environment are important factors influencing job satisfaction levels, which ultimately impact a person's intention to voluntarily leave the company. The research method used was a quantitative approach, with data collection using a survey method through questionnaires distributed to employees. The population used was 130, with a sampling technique using the Slovin formula, resulting in a sample of 98 respondents. The data analysis technique in this study used Partial Least Squares (PLS) using SmartPLS software version 4.0. PLS is a Structural Equation Modeling (SEM) method. The results of this study are expected to influence compensation and the work environment on job satisfaction, and that job satisfaction plays a role in reducing turnover intention.